Hydrogen bonding at C=Se acceptors in selenoureas, selenoamides and selones. Issue 3 (17th May 2016) - Bibelayi, Dikima; Lundemba, Albert S.; Allen, Frank H.; Galek, Peter T. A.; Pradon, Juliette; Reilly, Anthony M.; Groom, Colin R.; Yav, Zéphyrin G.
Abstract : The hydrogen‐bonding ability of C=Se acceptors in selenoureas, selenoamides and selones has been probed using a combination of a Cambridge Structural Database analysis and ab initio calculations, showing that these C=Se acceptors are similar in behaviour to their sulfur analogues, and should therefore have similar use in crystal engineering as C=S acceptors. Abstract : In recent years there has been considerable interest in chalcogen and hydrogen bonding involving Se atoms, but a general understanding of their nature and behaviour has yet to emerge. In the present work, the hydrogen‐bonding ability and nature of Se atoms in selenourea derivatives, selenoamides and selones has been explored using analysis of the Cambridge Structural Database and ab initio calculations. In the CSD there are 70 C=Se structures forming hydrogen bonds, all of them selenourea derivatives or selenoamides. Analysis of intramolecular geometries and ab initio partial charges show that this bonding stems from resonance‐induced C δ+ =Se δ− dipoles, much like hydrogen bonding to C=S acceptors. C=Se acceptors are in many respects similar to C=S acceptors, with similar vdW‐normalized hydrogen‐bond lengths and calculated interaction strengths. The similarity between the C=S and C=Se acceptors for hydrogen bonding should inform and guide the use of C=Se in crystal engineering.